Indole-3-Aldehyde Reduces Inflammatory Responses and Restores Intestinal Epithelial Barrier Function Partially via Aryl Hydrocarbon Receptor (AhR) in Experimental Colitis Models - Wang M; Guo J; Hart AL; Li JV (Journal of Inflammation Research, 2023)
Mu Wang,1,2,* Jian Guo,3,* Ailsa L Hart,4 Jia V Li1 1Section of Nutrition, Division of Digestive Diseases, Department of Metabolism, Digestion and Reproduction, Faculty of Medicine, Imperial College London, London, W12 0NN, UK; 2Department of Neurology, Shanxi Provincial People’s Hospital, the Affiliated People’s Hospital of Shanxi Medical University, Taiyuan, Shanxi Province, 030012, People’s Republic of China; 3Department of General Surgery, Shanxi Provincial People’s Hospital, the Affiliated People’s Hospital of Shanxi Medical University, Taiyuan, Shanxi Province, 030012, People’s Republic of China; 4IBD Unit, St. Mark’s Hospital, London, HA1 3UJ, UK*These authors contributed equally to this workCorrespondence: Jia V Li, Section of Nutrition, Division of Digestive Diseases, Department of Metabolism, Digestion and Reproduction, Faculty of Medicine, Imperial College London, London, W12 0NN, UK, Tel +44 20 7594 3230, Email jia.li@imperial.ac.ukPurpose: Indole-3-aldehyde (IAld) has been shown to improve intestinal epithelial barrier (IEB) function through the aryl hydrocarbon receptor (AhR) in murine colitis models. However, the impact of IAld on intestinal tissue inflammation remains unexplored. This study aimed to investigate the effects of IAld on the inflammatory responses of the gut both in vivo and in vitro and probe the mechanisms by which IAld attenuates colitis.Methods: The effects of IAld on phenotypic changes, pro-inflammatory cytokines, IEB functions and the faecal bacterial composition in mice with dextran sulfate sodium salt (DSS)-induced colitis were assessed. Macrophage cells and intestinal epithelial cells were stimulated with lipopolysaccharide (LPS), and the effects of IAld on the inflammatory responses and IBE functions were measured.Results: IAld reduced IL-6, IL-1β and TNF-α protein levels in both colonic tissues from the mice with colitis and LPS-stimulated macrophage cells. The IAld-mediated reduction of IL-6 but not IL-1β and TNF-α was through AhR activation. Furthermore, nuclear factor-κB pathway was found to be inhibited by IAld treatment via AhR activation both in vivo and in vitro. Gut permeability was significantly improved by IAld in both DSS-treated mice and LPS-stimulated Caco-2 cells. This observation is consistent with downregulation of phosphorylated myosin light chain through AhR activation. IAld did not appear to have an effect on the bacterial composition in mice with colitis despite the reduced colonic inflammatory responses.Conclusion: IAld improved DSS-induced colitis by inhibiting the inflammatory responses and restoring IEB function, partially via AhR activation. This work provided insight into the function of IAld in modulating gut inflammation. Keywords: indole-3-aldehyde aryl hydrocarbon receptor intestinal inflammation